Influence of the Role of Mentoring and Internal Training on Improving Access to Financial Services for Small and Medium Enterprises (SMEs) in Business Credit Financing: (Case Study At Bank Aceh Syariah Tapaktuan Branch) - Hasanah, Selfi Ulfa; Syahriza, Rahmi; Ahmad Syakir (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
In an effort to broaden SME access to banking services, this research will examine how mentorship and training programs have affected business credit financing at the Bank Aceh Syariah Tapaktuan Branch. The effects may be gradual or noticeable all at once. The researchers used SPSS, a statistical program, to conduct a descriptive quantitative analysis. Questionnaires were sent to suitable research samples to gather data. A total of thirty small and medium-sized enterprises (SMEs) from the Syariah Tapaktuan Branch of Bank Aceh comprised the study's population. This research found that training and the role of mentors are important factors in determining whether a company can secure a loan. There is a positive correlation between these two factors and business credit financing when considered collectively. This research aims to support the claim that Bank Aceh Syariah's training and mentoring programs help SMEs develop efficiently and sustainably by increasing their access to business credit financing.